Rekayasa Mobile Sprayer Machine untuk Pemeliharaan Tanaman Tebu Lahan Kering - Gatot Pramuhadi; Mohammad Yanuar Jarwadi Purwanto; Agus Sutejo (Institut Pertanian Bogor, 2014)
In order to raise sugarcane productivity and milling yield, it must be applied a mobile sprayer machine in asugarcane dry land to apply nutrition droplets on plants rows that it can follows vegetative and generative plantsgrowths until nearly harvesting time. The objective of the research was to design a mobile sprayer machine. Resultof the design was a prototype A (mobile sprayer machine based on a motorcycle). Test result of the prototype Ashowed that spraying flow rate increased from 3.79 6.71 l/minute by increasing liquid pressure from 2 7 kgf/cm2,so that operating time of the machine with 50 l capacity were 7.46 13.20 minutes. Test result in the PG Subangsugarcane area showed that the prototype A was difficult to control, but it still could accelerate on between plantsrows with average forward speed of 0.32 0.76 m/second. It were operated on liquid load of 100 and 50 kg. Theprototype A was changed by a prototype B (mobile sprayer machine based on tri-cycle motorbike). Test result inthe PG Subang sugarcane area showed that the prototype B could accelerate smoothly with forward speed of 2.15m/second on a flat area, but it just had capability to accelerate with average forward speed of 0.24 m/second when itwas applied on three-months ratoon plants rows area.